Out of Court Settlement of Child Custody Disputes by Village Heads of Sambahule, South Konawe District: Legal Position, Procedure, and Implications - Nur Intan; Sahrina Safiuddin; Heryanti Heryanti; Jumiati Ukkas; LM Saleh Saputra; Ramadan Tabiu (Journal of Law, Social Science and Management, 2026)
Background: This study examines the role and legal authority of the village head in resolving child custody disputes through non-litigious mediation in Sambahule Village, Baito Sub-district, South Konawe Regency, Southeast Sulawesi Province, Indonesia. Objectives: The objectives of this study are to analyse the authority of village heads in determining child custody rights, explain the mechanism for resolving child custody disputes, and assess the social and legal implications of village head decisions. Method: Employing a normative-empirical legal research design with a qualitative descriptive approach, data were gathered through in-depth interviews, field observation, and documentary analysis. Results: The findings reveal two principal conclusions: first, the village head possesses no direct statutory authority to formally adjudicate child custody, as such jurisdiction is vested exclusively in the Religious Court (for Muslim parties) or the District Court (for non-Muslim parties) under Law No. 1 of 1974 on Marriage as amended by Law No. 16 of 2019, and the Compilation of Islamic Law (KHI) Article 105; second, notwithstanding this limitation, the village head's role as a community mediator grounded in Law Number 6 of 2014 on Villages, Article 26(4)(k) proved socially effective in the case under study, producing a consensual, peace-based resolution within two mediation sessions held in January 2021. Conclusion: The study further reveals that village-level decisions carry no binding legal force and remain subject to formal judicial challenge. The paper recommends clearer regulatory delineation of the village head's dispute-resolution authority, mandatory mediator certification, and post-mediation court ratification to secure the legal protection of the child's best interests. Keywords: child custody; village head authority; non-litigation; family dispute resolution; Islamic family law